2017
DOI: 10.1038/s41467-017-00299-9
|View full text |Cite
|
Sign up to set email alerts
|

An integrated bioinformatics platform for investigating the human E3 ubiquitin ligase-substrate interaction network

Abstract: The ubiquitination mediated by ubiquitin activating enzyme (E1), ubiquitin conjugating enzyme (E2), and ubiquitin ligase (E3) cascade is crucial to protein degradation, transcription regulation, and cell signaling in eukaryotic cells. The high specificity of ubiquitination is regulated by the interaction between E3 ubiquitin ligases and their target substrates. Unfortunately, the landscape of human E3-substrate network has not been systematically uncovered. Therefore, there is an urgent need to develop a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
157
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 57 publications
0
157
0
Order By: Relevance
“…Based on the interactome landscape from BioGRID, STIL may interact with ubiquitin‐specific protease 7 (USP7), which represses the auto‐ubiquitination of checkpoint with forkhead and ring finger domains (CHFR)‐E3 ubiquitin ligase . Intriguingly, SP3 was predicted as a high‐score substrate of CHFR by the UbiBrowser . Taken together, STIL regulates oncogenic IGF‐1/PI3K/AKT pathway in GC, which may attribute to its interaction with the USP7/CHFR/SP3 signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the interactome landscape from BioGRID, STIL may interact with ubiquitin‐specific protease 7 (USP7), which represses the auto‐ubiquitination of checkpoint with forkhead and ring finger domains (CHFR)‐E3 ubiquitin ligase . Intriguingly, SP3 was predicted as a high‐score substrate of CHFR by the UbiBrowser . Taken together, STIL regulates oncogenic IGF‐1/PI3K/AKT pathway in GC, which may attribute to its interaction with the USP7/CHFR/SP3 signaling axis.…”
Section: Discussionmentioning
confidence: 99%
“…Single gene GSEA based on the TCGA database was used to explore the pathway differences between samples with high and low expressions of VIM and ABCC1 [40]. The E3substrate interaction network (http://ubibrowser.ncpsb.org/) was used to predict the E3s of VIM and ABCC1 [41]. Equal amounts of protein samples were separated with 10% sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) and transferred onto polyvinylidene difluoride (PVDF) membranes.…”
Section: Lscc Transcriptomics Data and Statistical Analysismentioning
confidence: 99%
“…However, the mechanism underlying its downregulation in tumor progression has been unclear. We used UbiBrowser software (http://ubibrowser.ncpsb.org/ubibrowser/home/index) (42) to predict the E3 ubiquitin ligase of SIRT2 and found that SYVN1 (HRD1) was a candidate (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%